Potential hazards and risks associated with the aquaculture industry - ERONDU, E.S.; ANYANWU, P.E.2 (Advances in Aquaculture and Fisheries Management, 2020)
Aquaculture, the farming of aquatic organisms, is fraught with potential hazards and risks which are categorized into occupational, environmental, food safety and public health. This paper reviewed major hazards and risks associated with the aquaculture industry and proffered strategies for their management and control. Aquaculture stakeholders should therefore ensure that guidelines and policies which promote an environmentally friendly and sustainable industry are instituted and enforced.